A rare cause of rectal bleeding - Cheng, Hsing-Hung; Chen, Tsung-Wei; Chou, Jen-Wei (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Cheng HH, Chen TW, Chou JW. A rare cause of rectal bleeding. Turk J Gastroenterol 2019; 30(11): 984-5.